Adipokines influence the inflammatory balance in autoimmunity. Issue 2 (October 2015) - Hutcheson, Jack
Highlights: Adipose tissue is a rich depot of immune cells and bioactive adipokines. Obesity is associated with the severity of several autoimmune diseases. Several adipokines may provide novel biomarkers for autoimmune diseases. Abstract: Over the past few decades, our understanding of the role of adipose tissue has changed dramatically. Far from simply being a site of energy storage or a modulator of the endocrine system, adipose tissue has emerged as an important regulator of multiple important processes including inflammation. Adipokines are a diverse family of soluble mediators with a range of specific actions on the immune response. Autoimmune diseases are perpetuated by chronic inflammatory responses but the exact etiology of these diseases remains elusive. While researchers continue to investigate these causes, millions of people continue to suffer from chronic diseases. To this end, an increased interest has developed in the connection between adipose tissue-secreted proteins that influence inflammation and the onset and perpetuation of autoimmunity. This review will focus on recent advances in adipokine research with specific attention on a subset of adipokines that have been associated with autoimmune diseases.